Trial and error versus errorless learning of functional skills in patients with acute stroke. - Mount J; Pierce SR; Parker J; Diegidio R; Woessner R; Spiegel L (NeuroRehabilitation, 2007)
Objective: To compare the effectiveness of errorless learning versus trial and error learning for teaching activities of daily living to patients with acute stroke with or without explicit memory impairments. Design: Randomized crossover. Setting: Rehabilitation hospital. Participants: Thirty-three adult subjects following an acute stroke. Intervention: Subjects were taught to prepare a wheelchair for a transfer and to put on a sock with a sock-donner. Tasks were taught using errorless learning or trial and error learning. Explicit memory was assessed using the Neurobehavioral Cognitive Status Exam. Main Outcome Measures: Days until subject was able to demonstrate retention of the task, and success or failure at carry-over to a similar task. Results: No significant differences were found in days to retention for either functional task when taught using errorless learning or trial and error learning in subjects with or without explicit memory impairments. Carry-over was significantly better when trial and error learning was used for learning sock donning. Conclusions: When choosing the best learning method for patients undergoing rehabilitation for stroke, the nature of the task should be considered. Additional research is needed to identify the best approach for teaching activities of daily living and facilitating carry-over of learning in individuals with acute stroke.